Hubungan Kualitas Informasi Terhadap Kepuasan Pengguna Layanan Rekam Medis Elektronik (RME) di Rawat Jalan RSU Queen Latifa Yogyakarta: Hubungan Kualitas Informasi Terhadap Kepuasan Pengguna Layanan Rekam Medis Elektronik (RME) di Rawat Jalan RSU Queen Latifa Yogyakarta - Nasiatul Aisyah Salim; Ulfah Rizqie Miftah Hani; Sekar Ayu Runggandini (JOHAR (Journal of Hospital Administration Research), 2024)
Introduction: The application of electronic medical records is increasing in developing countries, including Indonesia. Electronic medical records are increasingly being implemented in hospitals to achieve improved service quality. The increasing number of hospital investments in information systems indicates that hospitals understand the importance of end-user and system-user satisfaction. User satisfaction is one way to determine the effectiveness and success of an information system. Research explains that information quality influences user satisfaction. Research objective: to determine the relationship between information quality and user satisfaction with electronic medical record services at outpatient hospital Queen Latifa Yogyakarta. Research Method: this research is quantitative. The population is officers who input medical record data into Sitiql (electronic medical records). The sampling technique uses accidental sampling. The sample was 81 people. The data collection technique uses a questionnaire. Data analysis uses Spearman rank. Research results: explain that the p-value is 0,596, namely that there is no relationship between the quality of information and the satisfaction of users of electronic medical record services at RSU Queen Latifa Yogyakarta. Conclusion: Information quality cannot increase user satisfaction with electronic medical record services at RSU Queen Latifa Yogyakarta.